Implementation of Complete Systematic Land Registration (PTSL) Financing Based on a Joint Decree of 3 Ministers (Medan Land Office Study) - Ingerti, Regita Sistiyani (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Complete Systematic Land Registration (PTSL) is one of the programs organized by the Government to assist communities in obtaining land certificates. The purpose of this study was to determine the financing procedure for Complete Systematic Land Registration (PTSL) based on the Joint Ministerial Decree, to determine the legal certainty of Complete Systematic Land Registration (PTSL) based on the Joint Ministerial Decree, to determine dispute resolution in complete systematic land registration. The writing of this thesis is descriptive and the approach used is empirical juridical research aimed at analyzing the problem by combining legal materials (which are secondary data) with primary data obtained in the field. The data collection tools are document studies and interviews and are analyzed qualitatively. The financing procedure for Complete Systematic Land Registration (PTSL) based on the Joint Ministerial Decree has determined the cost of preparation for implementation (document preparation activities, procurement of stakes and stamps, operational activities of kelurahan/village officers). PTSL for category III (North Sumatra) costs Rp. .- (one hundred ninety seven thousand one hundred and sixty rupiah). Legal certainty for Complete Systematic Land Registration (PTSL) based on a Joint Ministerial Decree is to provide legal protection to the holder of rights to a plot of land in the form of granting a certificate of land rights and provide information to interested parties so that it is easy to obtain data, both data and information. physical and juridical data that have been registered are open to the public as well as the implementation of an orderly administration, both in terms of transfer, encumbrance, and annulment of rights to land parcels. Dispute resolution in a complete systematic land registration is if there is an error in the data, both physical data and juridical data at the time of data announcement in the village/kelurahan, it can be corrected before a certificate is made, but if the certificate has been issued but there are data errors in it, the wrong data can be submitted. objections to the National Land Agency Office and can be resolved through litigation or non-litigation, namely through mediation or by means of the State Administrative Court.